2015
DOI: 10.1534/genetics.115.183137
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Regulators of Morphogenesis Common to Vertebrate Neural Tube Closure andCaenorhabditis elegansGastrulation

Abstract: Neural tube defects including spina bifida are common and severe congenital disorders. In mice, mutations in more than 200 genes can result in neural tube defects. We hypothesized that this large gene set might include genes whose homologs contribute to morphogenesis in diverse animals. To test this hypothesis, we screened a set of Caenorhabditis elegans homologs for roles in gastrulation, a topologically similar process to vertebrate neural tube closure. Both C. elegans gastrulation and vertebrate neural tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 103 publications
1
18
0
Order By: Relevance
“…The results confirm coevolution of cis-regulatory sites, gene structures and protein sequence over tens of millions of years of evolution. Many of the conserved features, including the DNA-binding domains, and binding sites for SKN-1, MED, and an Sp1-like factor, are consistent with known properties of the med and end genes in C. elegans (Maduro et al 2001;Maduro et al 2015;Sullivan-Brown et al 2016;Broitman-Maduro et al 2005). Prior work has also shown that orthologous meds and/or ends from a few of these species can function as transgenes in C. elegans (Coroian et al 2006;Maduro et al 2005a).…”
Section: Discussionsupporting
confidence: 57%
“…The results confirm coevolution of cis-regulatory sites, gene structures and protein sequence over tens of millions of years of evolution. Many of the conserved features, including the DNA-binding domains, and binding sites for SKN-1, MED, and an Sp1-like factor, are consistent with known properties of the med and end genes in C. elegans (Maduro et al 2001;Maduro et al 2015;Sullivan-Brown et al 2016;Broitman-Maduro et al 2005). Prior work has also shown that orthologous meds and/or ends from a few of these species can function as transgenes in C. elegans (Coroian et al 2006;Maduro et al 2005a).…”
Section: Discussionsupporting
confidence: 57%
“…In E, Wnt signaling further represses tbx-35 expression (Broitman- Maduro et al, 2006). studies revealed many novel regulators implied in endoderm development and embryogenesis (Witze et al, 2009;Du et al, 2014;Sullivan-Brown et al, 2016;Tintori et al, 2016;Dineen et al, 2018;Wiesenfahrt et al, 2018). The elucidation of C. elegans endoderm GRN provides a strong foundation from which to explore the diversification of endoderm GRN in other organisms.…”
Section: The C Elegans Endoderm Gene Regulatory Networkmentioning
confidence: 99%
“…There were five class 2 genes that, despite exhibiting an abnormal nuclear pattern, had normal (arx-1, arx-3, let-19, gex-2) or only slightly reduced (die-1) nuclear counts for the three germ layers, suggesting a primary defect in cell positioning and/or early morphogenesis. Three of these genes encode regulators of actin assembly: ARX-1 and ARX-3 are components of the Apr2/3 complex (Pollard, 2017;Sawa et al, 2003), and GEX-2 is a component of the WAVE complex, which regulates the Arp2/3 complex in response to Rac signaling (Patel et al, 2008;Soto et al, 2002;Sullivan-Brown et al, 2016). Consistent with previous work, knockdown of all three genes led to a ventral rupture phenotype, particularly well captured in the Morphogenesis strain, in which the epidermis compressed into a patch on the dorsal side of the embryo ( Fig.…”
Section: Custom Programs To Crop and Orient Individual Embryos For 4dmentioning
confidence: 99%